Embedded sensor networks for weather monitoring in UMP Pekan - Muhammad Razif, Noor Azam (2012)
This paper presents the implementation of the event-driven Embedded Sensor Network for weather monitoring which is used for environmental monitoring using temperature and humidity sensors.The current situation in Pekan town, especially in UMP Pekan Campus is that the weather is unpredictable and can be very unstable, due to its location. UMP Pekan sits near to the river mouth of Sungai Kuala Pahang and just a few meters away from the South China Sea.Sea wind brings along hot air from the ocean to the land during the day, and brings back cold air from the land to the sea during the night. These phenomenon, together with the huge variance in the humidity parameter, would definitely affect the livelihood of people living in UMP campus. Therefore, this work would like to propose a monitoring mechanism that takes reading samples at constant rates throughout its operation.The aim is to design a system that evaluates samples only when it is triggered by an outside event, which in this rain, hot air,wind, and cold air .The objective of this paper is to develop an embedded sensor network by modifying the programs that run the sensor networks. The embedded sensor network system that will be mechanism developed has variable sampling rates with interfaces to temperature sensors and humidity sensor. The developed system would provide an applicable device that can be used in Universiti Malaysia Pahang as an organised weather and environmental forecasting system.